GAMIEFECTS 2.0: um framework para avaliar aprendizagem a partir do uso da gamificação - Barnaski, Maria Rita Oliveira (2024)
This dissertation originates from the Graduate Program in Computer Science, belonging to the research line of Applied Computing, with the main objective of fulfilling a partial requirement to obtain the degree of Master in Computer Science. Since gamification has been used in recent years for various purposes, having great importance in education as a tool for effects such as motivation and engagement, it is necessary to have tools for the evaluation of its impacts. Thus, the first version of GAMIEFECTS was compiled, measuring the effects of the environment in relation to the user in a satisfactory way. However, it is necessary to have the addition of specific measures to measure one of the main intended effects of gamification: learning. With this, from the research on gamification and evaluative models, in addition to a mapping of methods and metrics collected, a new version of GAMIEFECTS was compiled, which was evaluated by a panel of experts from a questionnaire built using the GQM method. From the evaluation, it was possible to see that the model has inconsistencies in certain quality aspects, especially those related to usability and ambiguity. In addition, comments from the reviewers pointed out the lack of description of realistic uses of the framework in the documentation presented. However, even with these limitations, the model was evaluated as valid, flexible, authentic and comprehensible, showing itself as a tool with great potential for use even in this first form. Thus, it is planned to review the method entirely for any inconsistencies, and to investigate the indicated guidelines in realistic scenarios, to assess their practical feasibility. Afterwards, a new documentation will be written and then a new evaluation can be made on it’s quality aspects.